The Effect of Regular Exercise and Probiotic Milk Consumption on Blood Glucose Levels in Diabetes Mellitus Patients - Somad, Abdul; Detiana, Detiana; Lusiana, Lusiana; Yuliartini, Henny (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diabetes Mellitus (DM) is a chronic condition characterized by elevated blood glucose levels due to defects in insulin secretion or action. Type 2 Diabetes Mellitus (T2DM) is the most prevalent form, contributing to complications such as cardiovascular diseases, neuropathy, and retinopathy. Managing T2DM often involves lifestyle changes, including physical activity and dietary adjustments. Probiotic milk, containing beneficial microorganisms, has been studied for its potential to improve glycemic control in diabetic patients. However, while exercise and probiotics have been researched separately, their combined impact on blood glucose management remains underexplored. This study aimed to assess the effects of regular exercise and probiotic milk consumption on blood glucose levels in T2DM patients. Specifically, it sought to examine blood glucose changes before and after exercise, and after consuming probiotic milk. A quasi-experimental design with a one-group pre-test post-test approach was used. Fifty participants with T2DM were recruited using purposive sampling from the SP6 Sari Bungamas Community Health Center, Lahat Regency, Indonesia. Participants engaged in light physical activity three times a week for three months. After each session, they consumed probiotic milk, and their blood glucose levels were measured pre-exercise, post-exercise, and two hours after consumption. Paired t-tests were used to analyze the data. Regular exercise significantly lowered blood glucose levels (p-value = 0.016). However, probiotic milk consumption did not show a statistically significant effect on blood glucose levels (p-value = 0.55). Regular exercise significantly reduces blood glucose levels in T2DM patients. However, the effect of probiotic milk on blood glucose levels was inconsistent, warranting further research to determine its potential benefits.